Interaction of C2H4···(HX)3 (X = F, Cl, Br, I) and C6H6···3HCl - Yang, Jie; Li, Shaobo; Yao, Weiwei; Yin, Qiyi; Tian, Changan; Xie, Jinsong; Liu, Junsheng (Asian Journal of Chemistry, 2014)
We applied ab initio theoretical studies on the X-H···p bond complexes of C2H4···3HX (X = F, Cl, Br, I) and comparative analysis of the interaction capability of the p bond in the complexes of C2H4···3HCl and C6H6···3HCl. The results demonstrated that, C2H4···3HX (X = F, Cl, Br, I) with increasing halogen atomic number, the bond length have all increasing. However, the binding energy of complex present in the overall decreasing trend. The corresponding X-H···p interactions weaken, two kinds of p bond system each HCl given small gap electron interaction capabilities, the p bond in the C6H6 molecule was stronger in the C2H4 molecule.